STUDY OF THE TECHNOLOGY FOR EXTRACTING TUNGSTEN IN THE FORM OF A SEMI-FINISHED PRODUCT AND METALLIC FORM FROM INDUSTRIAL WASTE - Shodiev , Abbos; Boymurodov , Najmiddin; Ravshanov , Avaz (Sanoatda raqamli texnologiyalar, 2024)
The article outlines the problems associated with the occurrence of man-made waste and the priority tasks for solving them, analysis of the technology for the enrichment of tungsten-containing ores and their waste, study of the chemical and mineralogical composition of man-made tungsten-containing waste from the Ingichki mine.